Biomechanical modeling of the cardiovascular system - Armentano, Ricardo; Cabrera Fischer, Edmundo I.; Cymberknop, Leandro J. (IOP (Series). Release 6., 2019)
Modeling has provided not only answers to questions related to normal or pathological function but also predicted multiple adaptations of the total and individual dynamic structures that are included in cardiovascular research. The original idea of this book was to produce a textbook to be used for the course 'Modeling in Biomechanics and Mechanobiology', which is oriented to Artificial Organs and Tissue Engineering at Buenos Aires University, Argentina. This book brings together the challenges and experiences of academic scientists, leading engineers, industry researchers and students to enable them to analyse results of all aspects of biomechanics and biomedical engineering. It also provides a springboard to discuss the practical challenges and to propose solutions on this complex subject.